Preservação do feno de Brachiaria decumbens stapf cv. Basilisk submetido a tratamento com amônia anidra ou uréia - Rosa, Beneval; Reis, Ricardo Andrade [UNESP]; De Panizzi, Rita Cássia [UNESP]; De Mesquita, Albenones José; Jobim, Clóves Cabreira (My University, 1998)
This study was conducted to evaluate the effects of anhydrous ammonia (NH3) or urea treatment on the occurrence of fungi in hays of Brachiaria decumbens Stapf cv. Basilisk, baled and stored with different moisture contents. The following treatments were evaluated: T1= green forage, soon after the harvest; T2= hay with 25% of moisture, with evaluation before baling; T3= hay with 13% of moisture and untreated; T4= hay with 25% of moisture + .5% of NH3 in the DM T5= hay with 25% of moisture + 1% of NH3 in the DM; T6= hay with 25% of moisture + .9% of urea in the DM and T7= hay with 25% of moisture + 1.8% of urea in the DM. The treated hays stayed under plastic cover during 75 days, and samples were collected soon after the opening of the bales piles,and they were immediately analyzed in the laboratory. Eleven fungi were identified in different treatments, with high incidence of Aspergillus in the untreated hay, in the hay stored with 25% of moisture and treated with .5% NH3. The ammoniation totally reduced the occurrence of Helminthosporium and Nigrospora, but it did not control the occurrence of Cladosposrium and caused the occurrence of Penicillium in large intensity. The occurrence of Epicoccum, Curvularia, Phitomyces and Aspergillus genus were totally controlled by the treatment of hay with 1% of NH3; .9 and 1.8% of urea.
Preservation of Brachiaria decumbens stapf cv. Basilisk hays submitted to anhydrous ammonia and urea treatment
Keywords: Ammoniation; Anhydrous ammonia; Fungi; Moisture; Urea